2017
DOI: 10.3390/sym9050063
|View full text |Cite
|
Sign up to set email alerts
|

On the Charge Density Refinement of Odd-Order Multipoles Invariant under Crystal Point Group Symmetry

Abstract: Charge density studies utilise a multipolar expansion of the atomic density (and the associated atomic scattering factor) in order to model asphericity. Contributions of the individual multipoles to the atomic density are then refined as multipole population coefficients. Refinement of these coefficients pertaining to odd-order multipoles that are invariant under the crystal point-group symmetry is often problematic, with ill-defined values and correlations plaguing the convergence to a good model. These diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…After initial least-squares cycles of refinement to get the best estimates for the third- and fourth-order GC cumulants of the two halogen atoms, all 50 GC coefficients were kept fixed and ten radial parameters were least-squares optimized in model E. No symmetry constraints were imposed, as no compelling evidences can be found that the invariant harmonics ( Y 10 and Y 30 ) under the point symmetry of the group are somewhat ill-determined. 35 The results of the refinements are summarised in Table S1 ESI †…”
Section: Methodsmentioning
confidence: 99%
“…After initial least-squares cycles of refinement to get the best estimates for the third- and fourth-order GC cumulants of the two halogen atoms, all 50 GC coefficients were kept fixed and ten radial parameters were least-squares optimized in model E. No symmetry constraints were imposed, as no compelling evidences can be found that the invariant harmonics ( Y 10 and Y 30 ) under the point symmetry of the group are somewhat ill-determined. 35 The results of the refinements are summarised in Table S1 ESI †…”
Section: Methodsmentioning
confidence: 99%